DINAMIKA TOLERANSI DAN MODERASI BERAGAMA DALAM PENDIDIKAN ISLAM DI INDONESIA: ANALISIS KOMPARATIF - Nur Annisa Aulia; Raisa Zuhra Salsabila Awaluddin; Rifa Tsamrotul Marifah; Fitri Dwi Zuhrotunnisa (Raudhah - Proud To Be Professional, 2024)
This study aims to fill the research gap related to the implementation of effective educational strategies in increasing religious tolerance and moderation, which has not been explored empirically. The method used is library research with a qualitative approach. Data were collected from academic literature, articles, official documents, then analyzed using a comparative approach to compare educational strategies implemented in various Islamic institutions. The results showed that the integration of the concepts of religious tolerance and moderation in the Islamic education curriculum has improved the values of togetherness, patience and justice among students. The most effective educational strategies include contextual approaches, interfaith dialog and community activities. Factors such as social environment, government policies and socio-economic status play an important role in supporting the implementation of these strategies. The implications of the findings suggest the need for more comprehensive Islamic education curriculum development, teacher training to teach tolerance values, and collaboration between educational institutions and the community. This research contributes to the development of Islamic education theory by strengthening the role of education as an agent of social change.